(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
This study was conducted to evaluate the therapeutic effect of methanol extract Centella asiatica leaves by assaying the activities of diagnostic markers (aminotransferases) in the streptozotocin induced diabetic rats. The rats were divided into five groups with 6 rats in each group. The methanol extract of Centella asiatica leaves was orally administered at a dose of 300 mg/kg body weight (b.w), and glibenclamide was administered at a dose of 5 mg/kg b.w. The effect of methanol extract of Centella asiatica leaves on total protein and the activities of diagnostic marker enzymes aspartate aminotransferase (AST), alanine aminotransferase (ALT) were examined in the liver and kidney of control and experimental rats. The result showed a significant (p < 0.001) decrease in total protein concentration and increase in AST and ALT activities in the liver of diabetic rats whereas the levels were unaltered in the kidney of diabetic rats. The daily oral treatment of methanol extract of Centella asiatica leaves to diabetic rats for 30 days reversed the above changes in a significant (p < 0.001) manner. From our observations, we conclude that methanol extract of Centella asiatica leaves was able to restore the altered activities of aminotransferases. The obtained results were compared with glibenclamide, a standard antidiabetic drug. These results indicate that oral treatment with methanol extract of Centella asiatica leaves may be used to alleviate the liver functions impairment associated with diabetic condition.